Influence of microencapsulation with sweet whey and prebiotics on the survival of Bifidobacterium-BB-12 under simulated gastrointestinal conditions and heat treatments. Issue 2 (December 2015) - Pinto, Stephanie S.; Verruck, Silvani; Vieira, Cleide R.W.; Prudêncio, Elane S.; Amante, Edna Regina; Amboni, Renata D.M.C.
Abstract Bifidobacterium BB-12 was microencapsulated with sweet whey and two different prebiotics (inulin and polydextrose) and its survival was evaluated during spray drying and after exposure to simulated gastrointestinal conditions and heat treatments. The microcapsules produced only with sweet whey showed the highest viability after spray drying (9.54 log CFU g−1) and the highest encapsulation yield (95.43%). After exposure to simulated gastrointestinal conditions, the microcapsules prepared only with sweet whey and those prepared with sweet whey and inulin provided better protection of the bifidobacteria when compared with the free cells, with a reduction of 0.49 and 0.97 logs, respectively. On the other hand, the microcapsules produced with sweet whey and polydextrose showed the highest reduction level (2.45 logs) after simulated gastrointestinal conditions. Regarding the survival of probiotics under heat treatments, the microcapsules produced only with sweet whey conferred greater protective effect when compared to the free cells. However, the microcapsules produced with sweet whey and polydextrose did not confer any protection to the probiotic cells under heat treatments.